193. Adaptive radiotherapy in lung cancer: Dosimetric and clinical aspects. (December 2018) - Manco, L.; Fabbri, S.; Allouzi, A.A.; Malorgio, A.; Fiorica, F.; Turra, A.
Abstract : Purpose: The aim of this work is to evaluate if the standard ITV (Internal Target Volume) which was adopted by physician for patients with lung cancer, has a sufficient margin to maintain an optimal coverage of GTV (Gross Target Volume) during all treatment course[1] . This in order to decide if re-planning is necessary. Methods and materials: We considered 7 patients affected by adenocarcinoma lung cancer, treated in the Department of Radiation Oncology of Ferrara between 2013 and 2014. GTV and CTV (clinical target volume) was contoured by the physician and a non-personalized ITV was defined (with an expansion of 1 cm in cranium-caudal direction and 0.5 cm in other direction from CTV). For each patient 3D plan was available and several CBCT (from 7 to 9). Using MIM-MAESTRO software (MIM Soft-ware, Inc., Cleveland, OH, USA) the radiotherapist propagated GTV and PTV contours from pCT (planning CT) to each CBCT. To obtain accumulated DVH we first generated deformed dose and contours of pCT on CBCT, then we propagated contours and dose from the planned CT to the last CBCT. Results: To decide if replan might be necessary we evaluated mean coverage of GTV on accumulated DVH related to pCT (we considered the 95% of prescription dose). In 6 of 7 cases the difference in coverage was less than 2%; only in one patient is around 3%. For PTV, the differences in coverage was less than 5%. Conclusion: We could say that CBCT set up verification and correction for these kind of patients is enough to control GTV coverage. This is due to the fact that the security margin adopted for standard ITV is corrected. In adenocarcinoma lung cancer adaptive radiotherapy could not be necessary.